Hip Dysplasia in Adults: Surgical Correction vs. Conservative Treatment Options - Wiak, Iga; Banyś, Filip; Czyżewski, Filip; Bochen, Konrad; Dudek, Stanisław; Jasiński, Filip; Łukawski, Artur; Pasierb, Karolina; Szałajska, Julia; Wojtach, Klaudia (Quality in Sport, 2024)
Introduction: Developmental Dysplasia of the Hip (DDH) is an anatomical deformation resulting from abnormal formation of the structures that make up the hip joint. Due to abnormal biomechanics patients with hip dysplasia usually develop radiographic osteoarthritis. Aim of the study: Despite the introduction of screening tests in children, DDH remains an issue among adults. For this group of patients, it is essential to begin treatment as early as possible to prevent early-onset osteoarthritis of the hip joint. In adults it is often too late to implement non-invasive methods such as braces or orthoses. Therefore, in this study, we aim to describe other treatment options for adults with DDH, considering both surgical and non-surgical methods. In the following work, we present both the advantages and complications associated with these surgical methods. Additionally, we describe the non-surgical alternative method of progressive resistance training (PRT) and consider the possibilities of combining it with surgical techniques. We also discuss the potential for pharmacological treatment. Material and Methods: Review of studies available through open-access sources on PubMed, Google Scholar, and the National Library of Medicine. Conclusions: The decision to quickly implement an appropriate treatment plan is crucial for improving the patient’s quality of life. The choice of treatment method should consider the patient’s age and the severity of the disease. Adults with DDH are most often qualified for surgical procedures, which include periacetabular osteotomy (PAO) and total hip replacement (THR). However, for some patients, surgical procedures may be contraindicated or impossible, and in such cases, other non-invasive methods, such as resistance training or appropriate pharmacotherapy, should be considered. Keywords: hip joint, osteoarthritis, surgery, conservative therapy, hip, Surgical Correction